2018
DOI: 10.2147/copd.s167369
|View full text |Cite
|
Sign up to set email alerts
|

COPD assessment test and FEV<sub>1</sub>: do they predict oxygen uptake in COPD?

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) manifests itself in complex ways, with local and systemic effects; because of this, a multifactorial approach is needed for disease evaluation, in order to understand its severity and impact on each individual. Thus, our objective was to study the correlation between easily accessible variables, usually available in clinical practice, and maximum aerobic capacity, and to determine models for peak oxygen uptake (VO2peak) estimation in COPD patients.Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…Thus, the 6MWD seems to be more closely correlated with the %FEV1, rather than the %FVC. Our findings concerning the relationship between the 6MWD and age or CAT score were also consistent with those of previous reports [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the 6MWD seems to be more closely correlated with the %FEV1, rather than the %FVC. Our findings concerning the relationship between the 6MWD and age or CAT score were also consistent with those of previous reports [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, functional capacity was significantly reduced in patients with diseases compared with the control group. Similar values of VO 2 peak have been observed in other studies in patients with COPD (12.8 mL·kg −1 ·min −1 , 42 heart diseases (16–18 mL·kg −1 ·min −1 ) 43 and COVID‐19 (17.2 mL·kg −1 ·min −1 ) 44 . Interestingly, Carvalho‐Jr et al .…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, Carvalho‐Jr et al . found that patients with COPD who had lower FEV1 had lower VO 2 peak 42 . They concluded that FEV1 was a predictor of VO 2 peak to determine risk and severity in patients with COPD.…”
Section: Discussionmentioning
confidence: 97%
“…28,29 The CAT is composed of eight items (cough, phlegm, chest tightness, breathlessness, limited activities, confidence leaving home, sleeplessness and energy) purposed to evaluate and quantify the impact of symptoms in patients with COPD. The patients with COPD are classified into mild (6-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and very severe (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). 1 Regarding the DASI, the higher the scoring (maximal score: 58.2), the higher the estimated V O 2 , which represents a better physical fitness.…”
Section: First Assessment Daymentioning
confidence: 99%
“…Additionally, the CAT is useful to evaluate the individuals' health status, as well as the impact of exercise intolerance in daily routine, well-being and general health of these patients 1 and described an appliance that can be estimating the V O 2 peak. 15 Besides the high correlation with mortality predictors in patients with COPD such as the BODE, 16 the 6MWT also enables the evaluation of functional capacity, symptoms, as well as, cardiovascular variables that are also considered to be important to predict functional capacity. [16][17][18][19] The post-exercise heart rate (HR) recovery (off-kinetics) has been recognized as a predictor factor for exacerbation and mortality in multiple respiratory diseases (ie, COPD), and it is straightly related to functional capacity and quality of life.…”
Section: Introductionmentioning
confidence: 99%